The effect of health education on adolescent knowledge about cervical cancer prevention in SMP Muhammadiyah Pone - Fifi Ishak; Levana Sondakh; Bella Sabrina Kadir (PSPP JOURNALS, 2021)
This study aims to look at the knowledge of adolescents on cervical cancer prevention. This study uses a quasi-experimental, namely experimental activities that aim to determine the effect that is caused. The sample used total sampling with a sample of 18 people using a one group pre-test and post-test design. The data analysis technique used was the Wilcoxon test. The results of this study indicate that there is a significant effect of health education on the knowledge of adolescent girls with a P-value of 0.001 <(α) 0.05. In conclusion, there is an effect of health education on the knowledge of young women about cervical cancer prevention.